Building new states: Lessons from Eritrea - Göte Hansson (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
With the Derg's overthrow in 1991, Eritrea embarked on the construction of a new state. New economic institutions were created, and considerable reform undertaken. Problems in co-ordinating reform and reconstruction were largely avoided, mainly because of the institutional `clean slate' facing the country at independence and the high level of social solidarity and other social capital that characterize the country. A well-defined economic strategy, and careful use of aid, promised higher returns to investment (and fewer unsustainable projects) than found elsewhere in SSA. By the start of 1998, the country had achieved much in a short time. The 1998-2000 war threatens to undermine this achievement. The ashes of the war that ended in 1991 have reignited in a surprising and different way, and the fall out from the war endangers progress in development and democratization.
Keywords: O10; O55; 330; sub-Saharan Africa; Eritrea; conflict; economic reform; Staatsgründung; Wirtschaftsreform; Eritrea